IMPACTS OF LEISURE TRAVELS ON INDIVIDUALS - Samrat Hazra; I Ketut Suarta; Ni Made Rai Sukmawati; I.A.K. Werdika Damayanti (Journal of Applied Sciences in Travel and Hospitality, 2019)
This study discusses the impacts of leisure travels on individuals which is developed based on a qualitative study using a combination of qualitative survey, and in-depth interviews conducted to people who have traveled both domestic and/or international more than once. In general, travels effect individuals constructively in which leisure travel significantly impacts individuals' personal growth majoring in cognitive and affective domains; the expressions made such as to broaden life perspectives and way of thinking, promote an open mind, increase knowledge and wisdom. Change and personal growth occur by means of learning by which travels contribute and facilitate this process of individual development. Learning happens through experiences; travels facilitate opportunities to be away from the mundane, insert the element of dynamic, surprise and beyond expectation; thus, enable individuals to see matters more objectively beyond one’s habits and traditions. As to how far thoughts, attitudes and actions are in concurrence is yet another research topic to investigate. Nonetheless, leisure travel is encouraged as a means of indulging in an intelligent leisure.